Effect of nitrogen supplementation and Zilpaterol-HCl on urea recycling in steers consuming corn-based diets - Brake, D.W.; Jones, M.L.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Cattle have the innate ability to recycle nitrogen absorbed post-ruminally back to the rumen as endogenously synthesized urea. Urea returning to the rumen provides an additional opportunity for ruminal microbes to benefit from nitrogen absorbed postruminally. Urea recycling may provide a significant benefit to cattle when protein requirements of ruminal microbes are high or when large amounts of the dietary protein escape ruminal degradation.
Keywords: Beef; Nitrogen; Zilpaterol-HCl; Urea; Corn